2007
DOI: 10.1021/jp071451+
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Carbonization as a Method of Enhancing Catalytic Properties of Hemoglobin at the Fuel Cell Cathode

Abstract: Recently, there has been increased demand for a polymer electrolyte fuel cell (PEFC) that functions efficiently with far less or no Pt. In this study, the catalyst for the O 2 reduction at the cathode was formed by carbonizing hemoglobin, which could be abundantly and inexpensively obtained. A substantial enhancement of catalytic properties was achieved by a change in the carbonization process from one step to two steps. The PEFC using the carbonized hemoglobin formed in the modified carbonization process gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…We previously reported that the micropore development in the catalyst exposes the active site to the micropore surface and increases the number of active sites and, consequently, the activity. 11,12 In this study, the specific surface area increased with a decrease in the heat-treatment temperature of the hemoglobin pyropolymer; therefore, this was the determining factor for the increase in the activity. The increases in the specific surface area and the mean pore diameter possessed an additional effect for enhancing the activity due to the increase in the availability of O 2 molecules for the individual active sites inside the micropore of the catalyst.…”
Section: Resultsmentioning
confidence: 95%
“…We previously reported that the micropore development in the catalyst exposes the active site to the micropore surface and increases the number of active sites and, consequently, the activity. 11,12 In this study, the specific surface area increased with a decrease in the heat-treatment temperature of the hemoglobin pyropolymer; therefore, this was the determining factor for the increase in the activity. The increases in the specific surface area and the mean pore diameter possessed an additional effect for enhancing the activity due to the increase in the availability of O 2 molecules for the individual active sites inside the micropore of the catalyst.…”
Section: Resultsmentioning
confidence: 95%
“…Several groups have since developed Fe/N/C and Co/N/C electrocatalysts and their work has been summarized in a recent review [3]. Since this review was written, several researchers (including our group) have continued to follow Yeager's steps and obtained Fe and Co-based catalysts for the oxygen reduction reaction (ORR) that are active in fuel cell conditions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural biomass (e.g., soybean [19], silk fibroin [20], kidney bean [21], and hemoglobin [22]) and animal biowastes (e.g., fish scale [23] and animal blood [24]) as a direct precursor or the nitrogen source of catalytically ORR-active sites was thought as an effective pathway to fabricate the doped-carbon catalysts. More recently, Li et al also synthesized a doped carbon-based ORR catalyst with three-dimensional porous network via using hemin biomaterial as a single-source precursor and using self-assembled sodium chloride crystallines as the template [25].…”
Section: Introductionmentioning
confidence: 99%